2006
DOI: 10.1074/jbc.m601025200
|View full text |Cite
|
Sign up to set email alerts
|

Switch from Caspase-dependent to Caspase-independent Death during Heart Development

Abstract: Differentiated cardiomyocytes are resistant to caspase-dependent cell death; however, the mechanisms involved are still uncertain. We previously reported that low Apaf1 expression partially accounts for cardiomyocyte resistance to apoptosis. Here, we extend the knowledge on the molecular basis of cardiac resistance to caspase activation by showing that the whole caspase-dependent pathway is silenced during heart development. Experimental ischemia triggers caspase activation in embryonic cardiomyocytes and prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
55
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 56 publications
6
55
0
Order By: Relevance
“…exchanger-1 (NHE-1) inhibitor, reduced release of Endo G and I/R injury, suggesting that attenuation of Endo G release is cardioprotective. In addition, Bahi et al [118] demonstrated that Endo G was released from mitochondria and induced DNA damage, and importantly when Endo G was downregulated using siRNA, DNA damage was significantly reduced in adult cardiomyocytes during I/R. Collectively, these studies suggest that Endo G is a critical contributor to DNA degradation during I/R.…”
Section: Apoptosis-inducing Factor (Aif)mentioning
confidence: 90%
“…exchanger-1 (NHE-1) inhibitor, reduced release of Endo G and I/R injury, suggesting that attenuation of Endo G release is cardioprotective. In addition, Bahi et al [118] demonstrated that Endo G was released from mitochondria and induced DNA damage, and importantly when Endo G was downregulated using siRNA, DNA damage was significantly reduced in adult cardiomyocytes during I/R. Collectively, these studies suggest that Endo G is a critical contributor to DNA degradation during I/R.…”
Section: Apoptosis-inducing Factor (Aif)mentioning
confidence: 90%
“…EndoG knock-out mice have no defect in apoptotic DNA degradation (16,17), but this might be due to redundancy with CAD and additional nucleases (1,2,18). RNA interference experiments and genetic data in Saccharomyces cerevisiae support a role of EndoG in apoptosis (8,19,20). EndoG is also thought to function in a non-apoptotic form of programmed cell death (21).…”
mentioning
confidence: 97%
“…It is reported that AIF causes high molecular weight DNA fragmentation and chromatin condensation in cells and isolated nuclei in a caspase-independent manner [9,10]. Previous research by Bahi and coworkers has demonstrated that the release of EndoG together with AIF from mitochondria to cytosol in rat postnatal differentiated cardiomyocytes is induced by experimental ischemia and causes DNA degradation in cardiomyocytes thereafter [11]. However, the involvement of EndoG and AIF in cardiomyocytes with AKT2 inhibition during ischemia still remains unclear.…”
Section: Introductionmentioning
confidence: 99%